The value of histopathology combined with CapitalBio Mycobacterium real-time polymerase chain reaction test for diagnosing spinal tuberculosis - Yao, Liwei; Bu, Caifang; Zhang, Jinjuan; Zhang, Dandan (Frontiers in Medicine, 2023)
Purpose To evaluate the diagnostic efficacy of CapitalBio Mycobacterium real-time polymerase chain reaction assay (CapitalBio test) in spinal tuberculosis (STB). The value of histopathology combined with the CapitalBio test in diagnosing STB was also assessed. Methods We retrospectively analyzed the medical information of suspected STB. The sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and area under the curve (AUC) of histopathology, CapitalBio test, and histopathology combined with CapitalBio test were calculated to evaluate their diagnostic efficacy compared with a composite reference standard. Results A total of 222 suspected STB patients were included in the study. The sensitivity, specificity, PPV, NPV, and AUC of histopathology for STB were recorded to be 62.0, 98.0, 97.4, 68.3%, and 0.80, respectively. The sensitivity, specificity, PPV, NPV, and AUC of the CapitalBio test were 75.2, 98.0, 97.9, 76.7%, and 0.87, respectively, while that of histopathology combined with the CapitalBio test was 81.0, 96.0, 96.1, 80.8%, and 0.89, respectively. Conclusion Histopathology and CapitalBio test exhibited high accuracy and are recommended in diagnosing STB. Histopathology combined with the CapitalBio test might give the best efficacy in STB diagnosis.